The management of secondary mitral regurgitation in patients with heart failure: a joint position statement from the Heart Failure Association (HFA), European Association of Cardiovascular Imaging (EACVI), European Heart Rhythm Association (EHRA), and European Association of Percutaneous Cardiovascular Interventions (EAPCI) of the ESC. (18th March 2021) - Coats, Andrew J S; Anker, Stefan D; Baumbach, Andreas; Alfieri, Ottavio; von Bardeleben, Ralph Stephan; Bauersachs, Johann; Bax, Jeroen J; Boveda, Serge; Čelutkienė, Jelena; Cleland, John G; Dagres, Nikolaos; Deneke, Thomas; et al.
Abstract: Secondary (or functional) mitral regurgitation (SMR) occurs frequently in chronic heart failure (HF) with reduced left ventricular (LV) ejection fraction, resulting from LV remodelling that prevents coaptation of the valve leaflets. Secondary mitral regurgitation contributes to progression of the symptoms and signs of HF and confers worse prognosis. The management of HF patients with SMR is complex and requires timely referral to a multidisciplinary Heart Team. Optimization of pharmacological and device therapy according to guideline recommendations is crucial. Further management requires careful clinical and imaging assessment, addressing the anatomical and functional features of the mitral valve and left ventricle, overall HF status, and relevant comorbidities. Evidence concerning surgical correction of SMR is sparse and it is doubtful whether this approach improves prognosis. Transcatheter repair has emerged as a promising alternative, but the conflicting results of current randomized trials require careful interpretation. This collaborative position statement, developed by four key associations of the European Society of Cardiology—the Heart Failure Association (HFA), European Association of Percutaneous Cardiovascular Interventions (EAPCI), European Association of Cardiovascular Imaging (EACVI), and European Heart Rhythm Association (EHRA)—presents an updated practical approach to the evaluation and management of patients with HF and SMR based upon a Heart Team approach. Graphical abstract: